Spoken English discrimination (SED) training with multilingual Malaysians: effect of adaptive staircase procedure and background babble in high variability phonetic training. - Leong, Christine Xiang Ru (2017)
High variability phonetic training (HVPT) has been shown to improve non-native speakers’ perceptual performance in discriminating difficult second language phonemic contrasts (Bradlow, Akahane-Yamada, Pisoni, & Tohkura, 1999; Bradlow, Pisoni, Akahane-Yamada, & Tohkura, 1997; Lively, Logan, & Pisoni, 1993; Lively, Pisoni, Yamada, Tohkura, & Yamada, 1994; Logan, Lively, & Pisoni, 1991). The perceptual learning can be generalized to novel words (Wang & Munro, 2004), novel speakers (Nishi & Kewley-Port, 2007; Richie & Kewley-Port, 2008) and even to speech production (Bradlow et al., 1997). However, the rigidity of the laboratory training settings has limited applications to real life situations.